2006
DOI: 10.1002/chin.200612048
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Oxidation of Primary and Secondary Benzylic Alcohols to Carbonyl Compounds Catalyzed by H3PW12O40/SiO2 under an O2 Atmosphere.

Abstract: Oxidation O 0212 Photocatalytic Oxidation of Primary and Secondary Benzylic Alcohols to Carbonyl Compounds Catalyzed by H3PW12O40/SiO2 under an O2 Atmosphere. -An efficient and selective oxidation becomes possible under conditions A). -(FARHADI*, S.; AFSHARI, M.; MALEKI, M.; BABAZADEH, Z.; Tetrahedron Lett. 46 (2005) 49, 8483-8486; Dep. Chem., Lorestan Univ., Khoramabad, Iran; Eng.) -Mais 12-048

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…Similar, X-ray diffraction sample become reported via Culity et al [32] and Bhattacharyya et al [33]. The use of the Scherer equation [34] the common crystalline length of ZnO nanoparticles is found to be 20 nm. Diffraction pattern similar to impurities are determined to be absent.…”
Section: Resultssupporting
confidence: 84%
“…Similar, X-ray diffraction sample become reported via Culity et al [32] and Bhattacharyya et al [33]. The use of the Scherer equation [34] the common crystalline length of ZnO nanoparticles is found to be 20 nm. Diffraction pattern similar to impurities are determined to be absent.…”
Section: Resultssupporting
confidence: 84%
“…The production of carbonylic compounds from the oxidation of primary and secondary benzylic alcohols, selectively and in high yields, was also achieved using (nBu 4 N) 4 W 10 O 32 , 272 H 3 PW 12 O 40 , 273 or H 4 SiW 12 O 40 encapsulated into silica matrixes. 274 Yields in the range 50-97% were obtained. Comparison with the unsupported materials showed that the composite photocatalysts were significantly more active.…”
Section: Polyoxometallatesmentioning
confidence: 98%
“…In fact, the higher surface area of the mesoporous material favored the conversion of cyclohexanol to the corresponding cyclohexanone, affording a higher final ratio ketone/alcohol (2.4). Another tungsten-based heteropolyoxometalate supported on amorphous silica (H 3 PW 12 O 40 /SiO 2 ) was successfully used for the selective aerobic photocatalytic oxidation of benzylic alcohols to the corresponding aldehydes and ketones, with yields up to 97 % (Farhadi et al, 2005). Even more interesting, in spite of the higher reactivity of carbonylic derivatives, no overoxidation was observed, and no traces of carboxylic acids were found in the final products (Eq.…”
Section: Oxidation Reactionsmentioning
confidence: 99%